Comparative assessment of salivary level of cortisol, anxiety and depression in patients with oral lichen planus - Jafari Soudeh; Baharvand Maryam; Jarahzade Maryam; Namdari Mahshid; Hojjat Pardis; Alimohammadi Marzieh (EDP Sciences, 2023)
Oral lichen planus (OLP) is an inflammatory condition of oral mucosa and skin. The present study compared salivary cortisol, depression and anxiety levels of patients with erosive and reticular OLP and healthy controls. In this case-control trial, 69 individuals (23 healthy, 23 erosive OLP and 23 reticular OLP patients) were selected. The participants completed the hospital anxiety and depression scale (HADS) and 5 mL of their unstimulated saliva were collected. Salivary cortisol levels were measured by enzyme-linked immunosorbent assay(ELISA). The comparison of anxiety and depression scores as well as salivary cortisol levels was done one-way analysis of variance (ANOVA) test while the paired comparisons were done by Turkey post hoc test. The mean anxiety score in erosive OLP patients was significantly higher than that in the control and reticular OLP groups. The reticular OLP and control groups had no significant difference in this respect. The three groups were not significantly different regarding the depression score or salivary level of cortisol. The correlation between depression and anxiety was significant but salivary level of cortisol had no correlation with anxiety or depression. This study showed that anxiety control may aid in control of erosive OLP, although further investigations are required.